International Imbalances and International Adjustment during the Global Financial Crisis - Klusáková, Petra (2014)
Despite the fact that international imbalances are not a new phenomenon, their development after the year 2000 has brought a new wave of debates addressing their role in the global economy and the recent financial crisis. After the year 2000 international imbalances started to rise dramatically. However, the situation changed with the arrival of the global financial crisis when the current account's positions narrowed significantly. My aim is to asses if the pre-crisis imbalances reflected rational behaviour of countries or if their extent exceeded levels consistent with sustainable current account positions. If the latter is true, did the adjustment process correct these excesses? By creating a proxy for the excessive part of the current account I find that a significant part of the excesses closed during the crisis and that even nowadays current account imbalances do not reach pre-crisis peak's values anymore. The results also reveal that the adjustment process was the most severe in the case of deficit and advanced countries. Next I analyse the channels through which this adjustment has taken place and I conclude that the contraction of current account imbalances was caused by a mixture of output, demand and income growth changes. In my sample, the adjustment of exchange rate seems to have no explanatory power as far as the current account contraction is concerned. Finally I focus on identifying the root causes of the global imbalances and the importance of adopting changes in the international monetary and financial system. I conclude that these reforms are crucial for preventing the global imbalances from re-accumulation.